2022
DOI: 10.3389/fimmu.2022.880959
|View full text |Cite
|
Sign up to set email alerts
|

Increased tumor glycolysis is associated with decreased immune infiltration across human solid tumors

Abstract: Response to immunotherapy across multiple cancer types is approximately 25%, with some tumor types showing increased response rates compared to others (i.e. response rates in melanoma and non-small cell lung cancer (NSCLC) are typically 30-60%). Patients whose tumors are resistant to immunotherapy often lack high levels of pre-existing inflammation in the tumor microenvironment. Increased tumor glycolysis, acting through glucose deprivation and lactic acid accumulation, has been shown to have pleiotropic immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…Interestingly, previous studies have found that the expression of tumor glycolysis-related genes is inversely associated with immune-related genes in multiple solid tumor types. High tumor glycolysis is associated with low immune infiltration and poor prognosis 50 . A plethora of empirical evidence robustly substantiates the conjecture that the intricacy and variety inherent in the tumor microenvironment's immune milieu possesses the capacity to significantly impact both tumorigenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have found that the expression of tumor glycolysis-related genes is inversely associated with immune-related genes in multiple solid tumor types. High tumor glycolysis is associated with low immune infiltration and poor prognosis 50 . A plethora of empirical evidence robustly substantiates the conjecture that the intricacy and variety inherent in the tumor microenvironment's immune milieu possesses the capacity to significantly impact both tumorigenesis and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is an apparent trend in the glycolytic phenotype being the most sensitive or responsive to autophagic inhibition. It has been presented as a consistent predictor in blood cancers ( Chen et al, 2014b ) and solid tumours ( Cohen et al, 2022 ). However, it is suggested efficacy would be increased as an adjuvant with some of the frontline chemotherapeutics that result in a shift in metabolic programming as a means of evading their effects, such as Cisplatin ( Xu et al, 2022 ), 5FU ( Denise et al, 2015 ) and Doxorubicin ( McGuirk et al, 2021 ).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In TME, whether oxygen is sufficient or not, tumor cells make use of plenty of glucose for glycolysis to generate lactic acid (30)(31)(32). As we all know, hypoxia-inducible factor-1 (HIF-1) induced by hypoxia can determine the modes of glucose metabolism, and a variety of substances in TME increase the amount of HIF-1 protein and also promote glycolysis (30).…”
Section: Glucose Metabolismmentioning
confidence: 99%